A Distributed Anchor Node Selection Algorithm Based on Error Analysis for Trilateration Localization. (5th December 2018) - Fan, Yingsheng; Qi, Xiaogang; Yu, Baoguo; Liu, Lifang
Abstract : This paper proposes a distributed anchor node selection algorithm based on error analysis for trilateration localization (EATL). The influence of distance measurement error on localization accuracy is discussed from two aspects: condition number of triangle formed by the three anchor nodes and the relative position between the unknown node and the three anchor nodes. Based on the error analysis, three principles for optimizing the selection of anchor nodes are given and then an algorithm for selecting anchor nodes on the ring is proposed.